ดุลยภาพระหว่างกฎหมายและคุณธรรม: จริยธรรมวิชาชีพทนายความยุคดิจิทัล - กันยาวรรณ, พิชิต (วารสาร มมร ยศสุนทรปริทรรศน์; Vol 2 No 2 (2025): วารสาร มมร ยศสุนทรปริทรรศน์-ปีที่ 2 ฉบับที่ 2 (พฤษภาคม-สิงหาคม 2568), 2025)
In the 21 st century, the role of lawyers has confronted a paradigmatic transformation driven by digital technological advancement, generating both opportunities and significant challenges to professional ethical standards. This study aims to analyze the equilibrium between law and morality within the context of legal practice in the digital era, employing jurisprudential and applied ethics theoretical frameworks, while referencing both national and international professional ethical standards, including the Code of Ethics for Lawyers of the Law Society of Thailand under Royal Patronage and the American Bar Association Model Rules of Professional Conduct. The research methodology employs documentary research and content analysis to synthesize knowledge and relevant case studies in this domain. The findings indicate that maintaining equilibrium between legal principles and ethical standards plays a crucial role in establishing professional credibility and enhancing occupational integrity. While legal frameworks serve as regulatory guidelines for enforcement and behavioral control, ethical principles complement professional practice by ensuring alignment with humanitarian values and reflecting society's desirable moral standards. Nevertheless, within the context of the digital technological era, emerging challenges have surfaced and significantly impacted the application of these fundamental principles, including the use of AI and LegalTech that may compromise client confidentiality, online legal advertising that risks breaching professional conduct, and the integration of digital evidence that may conflict with standards of accuracy. This article proposes proactive measures to strengthen ethics, such as modernizing professional regulations, providing continuous training in technology and ethics, and fostering an organizational culture grounded in morality. These measures will enable lawyers to adapt effectively while preserving ethical standards amidst technological change.